Improvement of Accuracy of Extraction of Radiation Patterns from FDTD Modelling of Axisymmetrical Antennas - Olszewska, M.; Gwarek, W. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a discussion on the accuracy of extraction of radiation patterns of BOR antennas from FDTD simulations. The effect of the “main beam shadow” causing errors in extracted back radiation is explained. The methods of its elimination are proposed.